Adenomatous polyposis coli heterozygous knockout mice display hypoactivity and age-dependent working memory deficits - Koshimizu, Hisatsugu; Fukui, Yasuyuki; Takao, Keizo; Ohira, Koji; Tanda, Koichi; Nakanishi, Kazuo; Toyama, Keiko; Oshima, Masanobu; Taketo, Makoto M.; Miyakawa, Tsuyoshi (Frontiers in Behavioral Neuroscience, 2011)
A tumor suppressor gene, Adenomatous polyposis coli (Apc), is expressed in the nervous system from embryonic to adulthood stage, and transmits the Wnt signaling pathway in which schizophrenia susceptibility genes, including T-cell factor 4 (TCF4) and calcineurin (CN), are involved. However, the functions of Apc in the nervous system are largely unknown. In this study, as the first evaluation of Apc function in the nervous system, we have investigated the behavioral significance of the Apc gene, applying a battery of behavioral tests to Apc heterozygous knockout (Apc+/−) mice. Apc+/− mice showed no significant impairment in neurological reflexes or sensory and motor abilities. In various tests, including light/dark transition, open-field, social interaction, eight-arm radial maze, and fear conditioning tests, Apc+/− mice exhibited hypoactivity. In the eight-arm radial maze, Apc+/− mice 7 to 11 weeks of age displayed almost normal performance, whereas those 11 to 14 weeks of age showed a severe performance deficit in working memory, suggesting that Apc is involved in working memory performance in an age-dependent manner. The possibility that anemia, which Apc+/− mice develop by 17 weeks of age, impairs working memory performance, however, cannot be excluded. Our results suggest that Apc plays a role in the regulation of locomotor activity and presumably working memory performance.